191k views
5 votes
9(x – 6) ≥ 2(x – 13)

User HashPsi
by
6.1k points

2 Answers

2 votes

Answer:

Explanation:

Simplify 9(x +1).

9x+9=5−2(9x+6)

Simplify 5−2(9x+6).

9x+9=−18x−7

Move all terms containing x to the left side of the equation.

27x+9=−7

Move all terms not containing x to the right side of the equation.

27x=−16

Divide each term by 27 and simplify.

x

=

16

27

The result can be shown in multiple forms.

Exact Form:

x=−16/27

Decimal Form:

x=−0.¯¯¯¯¯¯

592

User OMi Shah
by
5.9k points
6 votes

Answer:

9x-54 ≥ 2x-26

This is true 9x-54 is greater or equal to 2x-26.

Explanation:

Have a nice day!

User RadamHussein
by
5.9k points